Construction of Combinatorial Ã¢â‚¬Å“LibraryÃ¢â‚¬Â of Cyclopeptides and Screening for Biological Activities - Chee Kheng, Teh,; Yusof, Rohana; Abd. Rahman, Noorsaadah (Malaysian Journal of Science, 2003)
Two combinatorial libraries of hexa- and heptacyclopeptides were synthesised by the split and mixed method. These libraries were tested for antibacterial activity against the bacterial strains Escherichia coli 25922, Escherichia coli 35213, Slaphyloccus aureus 24213 and Staphyloccus aureus 29213. Results indicated that these cyclopeptides demonstrated no activities against all four bacterial strains tested. Preliminary screening of the libraries against dengue virus protease however indicated some inhibitory activities from compounds in both libraries.Two combinatorial libraries of hexa- and heptacyclopeptides were synthesised by the split and mixed method. These libraries were tested for antibacterial activity against the bacterial strains Escherichia coli 25922, Escherichia coli 35213, Slaphyloccus aureus 24213 and Staphyloccus aureus 29213. Results indicated that these cyclopeptides demonstrated no activities against all four bacterial strains tested. Preliminary screening of the libraries against dengue virus protease however indicated some inhibitory activities from compounds in both libraries.